2004
DOI: 10.1158/1055-9965.epi-03-0196
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 Mutations in Women from Shanghai China

Abstract: Little is known about the frequency of germ-line mutations in the breast cancer susceptibility genes BRCA1 and BRCA2 among Asian populations. We investigated the distribution of BRCA1 and BRCA2 germline mutations and polymorphisms in a cohort of women from Shanghai, China.Study subjects totaled 1306, and included 645 women with breast cancer, 342 women with benign breast disease, and 319 unaffected controls, born between 1924 and 1958, selected from women enrolled in a randomized trial of Breast Self-Examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
62
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 36 publications
13
62
3
1
Order By: Relevance
“…Of those interviewed, 470 (85%) women with fibrocystic conditions and 323 (86%) women with breast cancer provided a blood sample. Additionally, women with breast cancer diagnosed from November 1989 to September 1995 were selected from a study of BRCA1 and BRCA2 mutations, which was designed to retrospectively recruit diagnosed cases of breast cancer under age 45, along with an equal number of older cases (Suter et al [56]). Retrospective recruitment was possible because in the BSE cohort, the average probability of survival from breast cancer for six years after diagnosis was greater than 80% (Thomas et al [52]).…”
Section: Study Population and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those interviewed, 470 (85%) women with fibrocystic conditions and 323 (86%) women with breast cancer provided a blood sample. Additionally, women with breast cancer diagnosed from November 1989 to September 1995 were selected from a study of BRCA1 and BRCA2 mutations, which was designed to retrospectively recruit diagnosed cases of breast cancer under age 45, along with an equal number of older cases (Suter et al [56]). Retrospective recruitment was possible because in the BSE cohort, the average probability of survival from breast cancer for six years after diagnosis was greater than 80% (Thomas et al [52]).…”
Section: Study Population and Settingmentioning
confidence: 99%
“…Genomic DNA was isolated from buffy coat using a salt-precipitation (Miller et al [58]) or a phenol-chloroform method (Suter et al [56];Bell et al [59];Maniatis et al [60]), or from whole blood (red cell solution) using the QIAamp® DNA Blood Midi Kit (Qiagen, Alameda, CA). DNA concentration was determined by UV spectrophotometry.…”
Section: Genotyping Assaysmentioning
confidence: 99%
“…However, our current understanding of BRCA1 mutations and their contribution to sporadic early-onset breast cancer (<35 years old) has arisen primarily from studies conducted in Caucasian women. To date, the little knowledge we have of BRCA1 germline mutations in Chinese women with early-onset breast cancer is mainly derived from Shanghai and Hong Kong (Tang et al, 1999;Suter et al, 2004). However, information on BRCA1 mutations in Uighur women with sporadic early-onset breast cancer is largely lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with rates in other Asian ethnic groups (Hall et al, 2009). Another study, by Suter et al (2004) found that the rates of BRCA1 mutations in sporadic breast cancers were 0.7% (4/590) in Shanghai of China. Moreover, in early-onset breast cancer, mutation rates of these genes were 5.1% in east regions of China (Li et al, 2008).…”
Section: Brca1 Gene Exon 11 Mutations In Uighur Andmentioning
confidence: 99%
“…Although the entire incidence of breast cancer is lower in Chinese women as compared with Caucasian women, early-onset breast cancer is, however, more common in Chinese women than Caucasian, and approximately 20% of breast cancer patients are diagnosed before the age of 40 years in Chinese women compared with 10% in Caucasian women 1) . In addition, approximately 10% of breast cancer patients have a family history of breast cancer in Chinese women 2) .…”
mentioning
confidence: 99%